Development of the Barthel Index 5 years after hip fracture: Results of a prospective study. Issue 8 (1st July 2019) - Knauf, Tom; Buecking, Benjamin; Hack, Juliana; Barthel, Juliane; Bliemel, Christopher; Aigner, Rene; Ruchholtz, Steffen; Eschbach, Daphne
Abstract : Aim: The importance of proximal femoral fractures is increasing due to demographic change. Despite appropriate care, these are associated with poor results. We are still lagging behind, and require information on the long‐term functional outcome of these patients and the predictive factors involved. Methods: Between 2009 and 2011, 402 patients aged >60 years with hip fractures were included in this prospective observational study. Patients were assessed with the Barthel Index before fracture, at discharge, and 6 months, 1 year and 5 years after surgery. In addition, a variety of parameters (sex, age, fracture type, American Society of Anesthesiologists classification, Mini‐Mental State Examination, housing situation, occurrence of complications during inpatient stay and type of care) were collected to identify the possible independent predictive factors using multivariate analysis. Results: The lowest Barthel Index was found at discharge (66 ± 24) for patients from an acute hospital. The Barthel Index improved within the first 6 months (86 ± 21) and decreased afterwards. The factors associated with a significantly higher point loss of the Barthel Index in the multivariate analysis were age ( P ‐value 0.020), pre‐fracture Barthel Index, ( P  ≤ 0.001), Mini‐Mental State Examination ( P  ≤ 0.001) and type II complications ( P = 0.001). The other values showed no significant influence on the Barthel Index. Conclusions: The present results showed that patients after a hip fracture have a great rehabilitation potential within the first 6 months after the event. More attention should be paid to type II complications and the occurrence of cognitive impairment. Both seem to be a surrogate parameter for the frailty of the patients.Geriatr Gerontol Int 2019; 19: 809–814 .